Effect of acupuncture on chronic bronchitis: A protocol for systematic review and meta-analysis - Mao, Dongdong (Medicine (Baltimore), 2020)
INTRODUCTION: Chronic bronchitis (CB) is a clinically common and recurrent respiratory disease. However, many trials have shown that acupuncture can effectively treat CB. There is currently no systematic review of this therapy. The plan is to evaluate the effectiveness and safety of this treatment in patients with CB. METHODS AND ANALYSIS: This systematic evaluation will entail an electronic and manual search of all acupuncture for CB from inception to December 31, 2020, regardless of the publication status or language. Databases include PubMed, Embase, Springer, Web of Science, the Cochrane Library, the World Health Organization International Clinical Trial Registration Platform, the Chinese Medicine Database, the China National Knowledge Infrastructure, the Chinese Biomedical Literature Database, the China Science Journal Database, and the Wanfang Database. Other sources of information, including bibliographies and meeting minutes for identified publications, will also be searched. A manual search for grey literature, including unpublished conference articles will be performed. Additionally, any clinical randomized controlled trials related to acupuncture for CB, regardless of the publication status and language limitations, will be included in the study. Study selection, data extraction, and research quality assessments will be conducted independently by 2 researchers. The main result was the Change in cystic fibrosis transmembrane conductance regulator function as measured by sweat chloride analysis or treatment effect. Secondary outcomes included Quality of life (eg, SF-36), change in Breathlessness, Cough, and Sputum Scale score, follow-up relapse rate, and adverse events. The system searches for randomized controlled trials of this therapy for CB. Implement the Cochrane RevMan V5.3 bias assessment tool to assess bias risk, data integration risk, meta-analysis risk, and subgroup analysis risk (if conditions are met). Mean difference, standard mean deviation, and binary data will be used to represent continuous results. RESULTS: This study will provide a comprehensive review and evaluation of the available evidence for the treatment of CB using this therapy. CONCLUSION: This study will provide new evidence to evaluate the effectiveness and side effects of acupuncture on CB. Because the data are not personalized, no formal ethical approval is required. PROSPERO REGISTRATION NUMBER: CRD42020170287